2015
DOI: 10.1021/jp511102y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Desorption Kinetics in Metal Intercalated Fullerides

Abstract: For different hydrogenated metal intercalated fullerides (Na 10 C 60 -H, Li 12 C 60 -H, and Li 28 C 60 -H) the activation energies for hydrogen desorption were determined by DSC. The Vyazovkin advanced method (VA) was used for the calculation of the reaction model free activation energy as a function of the extent of conversion α. Activation energies are highest for low α and decrease for increasing α, between around 200−145 and 245−175 kJ/mol for the Na and Li compounds, respectively. The decrease of activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 22 publications
5
40
0
Order By: Relevance
“…Reversible intercalation of Li or Na into the carbon can occur, stabilizing the metal phase and hence lowering the equilibrium decomposition temperature, for instance, that of NaH under 1 bar H 2 pressure from 425 to 225°C [154,171]. Also, lithium-and Nadoped fullerenes are capable of reversibly storing 5 wt% hydrogen [172,173].…”
Section: Insight Into Changes In Phase Equilibriamentioning
confidence: 99%
“…Reversible intercalation of Li or Na into the carbon can occur, stabilizing the metal phase and hence lowering the equilibrium decomposition temperature, for instance, that of NaH under 1 bar H 2 pressure from 425 to 225°C [154,171]. Also, lithium-and Nadoped fullerenes are capable of reversibly storing 5 wt% hydrogen [172,173].…”
Section: Insight Into Changes In Phase Equilibriamentioning
confidence: 99%
“…Doping fullerenes with alkali or earth alkaline metals promises to elevate adsorption energies to several tenths of an eV [9,12,16]. Experiments have shown that as much as 5 wt% of H 2 could be reversibly adsorbed and desorbed in C 60 Li 6 and C 60 Li 12 ; the storage capacity of C 60 Na 6 and C 60 Na 10 was found to be slightly lower [17][18][19][20][21]. Moreover, desorption temperatures were reduced to about 260…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the temperature of the onset of desorption was reduced to about 250 -300 °C, well below the temperature (> 500 °C) at which hydrogen starts to desorb from pure fulleranes [33,34]. Optical spectroscopy, X-ray diffraction, neutron diffraction, NMR and Muon Spin Relaxation have been applied to probe the dynamics and structural changes that accompany ad-and desorption of hydrogen [23,[30][31][32][33][35][36][37][38][39]. Laser-desorption mass spectra of hydrogenated alkali-doped C60 solids show evidence for the presence of HnC60 (n up to 48) fulleranes [23]; other spectra show HnC60 + ions containing as many as 60 hydrogen atoms [32].…”
Section: Introductionmentioning
confidence: 92%
“…Experiments performed on bulk samples of lithium-and sodium intercalated C60 have proven enhanced values for hydrogen uptake compared to pure C60. As much as 5 wt % of H2 could be reversibly chemisorbed and desorbed in C60Li6 and C60Li12; the storage capacity of C60Na6 and C60Na10 was found to be slightly lower [22,[30][31][32][33]. Moreover, the temperature of the onset of desorption was reduced to about 250 -300 °C, well below the temperature (> 500 °C) at which hydrogen starts to desorb from pure fulleranes [33,34].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation